Materiomics : High-Throughput Screening of Biomaterial Properties. - De Boer, Jan (Cambridge University Press, 2013)
"This complete, yet concise, guide introduces you to the rapidly developing field of high throughput screening of biomaterials: materiomics. Bringing together the key concepts and methodologies used to determine biomaterial properties, you will understand the adaptation and application of materomics in areas such as rapid prototyping, lithography and combinatorial chemistry. Each chapter is written by internationally renowned experts, and includes tutorial paragraphs on topics such as biomaterial-banking, imaging, assay development, translational aspects, and informatics. Case studies of state-of-the-art experiments provide illustrative examples, whilst lists of key publications allow you to easily read up on the most relevant background material. Whether you are a professional scientist in industry, a student, or a researcher, this book is not to be missed if you are interested in the latest developments in biomaterials research"--Provided by publisher